Suitability assessment for siting water harvesting ponds: (Case of Erdenetsagaan soum, Sukhbaatar aimag) (Mongolian Journal of Agricultural Sciences, 2019)
This paper represents test results of methodology for identifying suitable sites for the water harvesting pondusing the "Multi-Criteria Analysis" in Geographical Information System. In order to do this, the objectives ofthe identification of harvesting sites were (i)to estimate constraint map (ii) to identify the multi-factor map and(iii) to measure the overall value of the suitability. According to the results of the assessment of the waterharvesting suitability, 10.23%or 173736 hectares area of Erdenetsagaan soum of Sukhbaatar aimag(province)are suitable, and 22.71% or 385534 ha area is moderately suitable, and 33.29%or 565198 ha land is limited forpond construction and 33.78% or 573532 ha territory is unsuitable for water harvesting.